Maternal mortality: a 6-year experience of the triumph achieved and the hardships faced in a tertiary care centre of Chhattisgarh - Nagaria, Tripti; Naik, Smrity; Punshi, Himani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Maternal death reflects the health care system of a country and majority of them are preventable. India’s MMR declined to 103 in 2017-19. However, SDG3 targets of reducing MMR to 30 is still far and a lot has to be done to achieve it. Methods: In this retrospective study, a 6-year analysis of the trends of maternal mortality for age group, booking status, parity, referral status, obstetric and non-obstetric causes of maternal death and the challenges faced in their management have been observed. The data obtained was tabulated and analysed for trends in maternal mortality over past 6 years. Results: Hypertensive disorders of pregnancy remains the major obstetric cause of death with significant decline in septic abortions. Liver and respiratory disorders have surpassed anemia as the major non-obstetric cause of death. A gradual shift from pulmonary edema to emergence of AKI and CVA as the immediate cause of death has been observed. Conclusions: Knowledge about fluid therapy, aggressive resuscitative measures and critical care management resulted in decline in cases of pulmonary edema. Improvement in anaemia at the cost of medical disorders was seen due to improved coverage of Iron folic acid prophylaxis, deworming and easy availability of blood banks. Trainings for ANMs and medical officers, early detection of warning signs, timely referrals, adolescent health clinics, improved booking status and increased institutional deliveries have led to reduction in MMR. Regular auditing of each maternal mortality can improve the scenario.